Pengaruh Literasi Keuangan, Efikasi Diri dan Kompetensi Kewirausahaan Terhadap Keberhasilan Usaha Mikro Kecil di Kecamatan Padang Timur - Salsabilla Audina Alwi; Riani Sukma Wijaya (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to find out that financial literacy, self-efficacy and entrepreneurial competence can influence the success of micro and small businesses and to find out how they influence them simultaneously. The research design used used quantitative methods. The subjects of this research are MSME business actors who have been running a business for at least 1 year. This research uses questionnaires that are distributed directly as data collection material. The sample in this research is 100 respondents, which are analyzed using SPSS 25. The results of this research show that financial literacy, self-efficacy and entrepreneurial competence have a positive effect on the success of micro and small businesses. In the F Test of financial literacy, self-efficacy and entrepreneurial competence simultaneously and significantly influence the success of micro and small businesses.